التشريعات الجديدة لمداخل المصرفية الإسلامية في الجزائر و موائمتها للمرجعية الفكرية الإسلامية - عمرانى, محمد (جامعة الوادي - University of Eloued, 2022)
تمثل الفروع الاسلامية التابعة للمصارف التقليدية اهم قطاعات العمل المصرفى الاسلامى و على الرغم من التوسع الهائل فى هذا المجال فى دول اسلامية وغيرها الا ان سؤال المشروعية يبقى قائما . الورقة البحثية التى بين ايدينا تندرج فى سياق الاجابة عن هذا السؤال و ما يقع من مستجدات على المصرفية الاسلامية فى الجزائر فى صورة التنظيمات التى سنها البنك المركزى فى الفترة الاخيرة بموافقة من الحكومة و التى افضت الى اطار قانونى يعتير الأول من نوعه و ابانت فيه الهيئة المسئولة عن رغبة اكيدة فى التوسع فى هذا النوع من البنوك والمؤسسات المالية، فبدات بالتاصيل النظرى لما جاءت به المساهمات الفكرية للاقتصاد الاسلامى منذ النشاءة الاولى للمصرف الاسلامى الى درجات متقدمة من الخدمات المصرفية الاسلامية ثم بيان ماجائت به التشريعات الاخيرة ثم مناقشة ابرز العناصر لتحقيق المشروعية. و تيبين ان النصوص الاخيرة تستجيب فى مجملها لمتطلبات المشروعية المعتمدة فى هذا المجال. banking. Despite the huge expansion in this field in Islamic countries and others, the question of legality remains. The Research paper before us falls within the context of answering this question and the developments in Islamic banking in Algeria in the form of the regulations enacted by the Central Bank in the recent period with the approval of the government, which led to a legal framework considered the first of its kind, in which the responsible body clarified From a firm desire to expand in this type of banks and financial institutions, It started with the theoretical rooting of what the intellectual contributions of the Islamic economy brought from the first inception of the Islamic bank to advanced degrees of Islamic banking services, then a statement of the recent legislation and then a The Islamic branches of traditional banks represent the most important sectors of Islamic discussion of the most prominent elements to achieve legitimacy. And it turns out that the recent texts respond in their entirety to the requirements of legality adopted in this field
New legislation for Islamic banking entrances in Algeria and its alignment with the Islamic intellectual reference
مقال
Keywords: نوافذ اسلامية؛ بنوك تقليدية؛ تنظيمات؛ تشريعات؛